Ameloblastic Fibroma of the Mandible Reconstructed with Autogenous Parietal Bone: Report of a Case and Literature Review - Conor Carroll; Mishaal Gill; Eleanor Bowden; John Ed O’Connell; Rajeev Shukla; Chris Sweet (Case Reports in Dentistry)
Ameloblastic fibroma (AF) is a rare, slow-growing benign neoplasm, comprised of tissues of odontogenic origin. It constitutes 2% of odontogenic tumours, occurring at any age, but has a predilection to present in the first two decades of life. AF principally affects the posterior mandible. It is characterized by epithelial islands and cords immersed in ectomesenchyme that mimics the dental papilla and enamel organ but without actual hard tissue formation. Herein, we describe the case of a 6-year-old Caucasian male who presented to the Oral and Maxillofacial Department at Alder Hey Children’s Hospital, Liverpool, UK, with a painless expansile mass in the left mandible which was diagnosed as a benign ameloblastic fibroma and subsequently enucleated and reconstructed with a parietal calvarial bone graft. A brief literature review and the issues surrounding diagnosis are discussed.